PENGARUH INTENSITAS ASET BIOLOGIS, LEVERAGE, UKURAN PERUSAHAAN, PROFITABILITAS TERHADAP KINERJA PERUSAHAAN - Benajir Singki; Harti Budi Yanti (STMIK Widuri Jakarta, 2025)
This study aims to analyze the effect of biological asset intensity, leverage, firm size and profitabilty on corporate performance in agricultural companies listed on the Indonesia Stock Exchange 2018-2020. This study uses panel data regression analysis techniques and the type of data used is secondary data published by the Indonesia Stock Exchange. The sample selection used the unbalance sample technique and obtained as many as 14 annual reports of agricultural companies to be studied. The results of the study found that Biological Asset Intensity, leverage, and profitability had no effect on corporate performance, while firm size had an effect on corporate performance.